2007
DOI: 10.1002/hec.1272
|View full text |Cite
|
Sign up to set email alerts
|

Equity in health and health care in a decentralised context: evidence from Canada

Abstract: The impact of administrative decentralisation on equity in health and health care is an important unresolved issue in the health policy debate. Predictions from the limited theoretical literature and the relevant empirical research are both insufficient to draw any firm conclusions. Many countries are nevertheless experimenting with decentralisation policies in the absence of research evidence. This paper presents an exploratory empirical analysis of decentralisation by investigating the spatial dimensions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 31 publications
7
49
2
1
Order By: Relevance
“…Our findings regarding income-related inequity in physician service use in Ontario, Canada are consistent with previous research (Allin, forthcoming; Asada and Kephart, 2007;Jiménez-Rubio et al, 2007;van Doorslaer et al, 2006) that has also found mild pro-rich inequity in the probability of a GP visit, pro-poor inequity in the conditional number of GP visits, and larger prorich inequity with respect to both the probability of and conditional number of visits to specialists.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings regarding income-related inequity in physician service use in Ontario, Canada are consistent with previous research (Allin, forthcoming; Asada and Kephart, 2007;Jiménez-Rubio et al, 2007;van Doorslaer et al, 2006) that has also found mild pro-rich inequity in the probability of a GP visit, pro-poor inequity in the conditional number of GP visits, and larger prorich inequity with respect to both the probability of and conditional number of visits to specialists.…”
Section: Discussionsupporting
confidence: 91%
“…Utilization of specialist services in Canada appears to be inequitable favouring the wealthier individuals, while use of GP services tends to be mildly, but significantly, pro-rich for the probability of a visit, and mildly pro-poor for the number of visits conditional on one visit (Allin, forthcoming; Asada and Kephart, 2007;Curtis and MacMinn, 2007;van Doorslaer et al, 2006;Jiménez-Rubio et al, 2007). While inequitable use of specialist care is evidenced in most countries, pro-rich inequity in the probability of a GP visit is unusual internationally (found in only three of 21 OECD countries studied -Canada, Portugal and Finland;van Doorslaer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…3 Nevertheless, we have to keep in mind that the bulk of the decentralization process occurred in 2002. 4 See, among many others, the collective work of Saltman et al (2007), the reviews of Jiménez-Rubio (2010) andandKolehmainen-Aitken (2005), the works of Bossert et al (2003) and Arreondo and Orozco (2005) for Latin American countries, the analyses of some African experiences by Jepsson and Okuonzi (2000) and Akin et al (2005), Tang and Bloom (2000) on China, Jiménez-Rubio et al (2008) and Zhong (2010) on Canada, Ferrario and Zanardi (2011) on Italy and Cantarero and Pascual (2006) on European Union countries.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in Canada have pointed to differential health service use by income category, [3][4][5][6][7] but to our knowledge, this is the first valid and reliable direct measure of cost-related barriers to necessary medical services. Although problems with health care affordability were more prevalent in low-than in highincome respondents in our sample, higher-income respondents also reported problems with affordability.…”
Section: Discussionmentioning
confidence: 96%
“…The publicly funded health system is a source of national pride for Canadians, 2 but evidence of health care inequity by socio-economic status in Canada [3][4][5][6][7] suggests that even medically necessary health care is not equally affordable. Health care affordability should be measured directly and monitored systematically.…”
Section: T He Accessibility Principle Enshrined In the 1984 Canadamentioning
confidence: 99%